2017
DOI: 10.1182/blood-2017-02-767285
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the higher rate of intracranial hemorrhage in glioma patients receiving therapeutic enoxaparin

Abstract: • Therapeutic enoxaparin was associated with a greater than threefold increased risk of major ICH in patients with glioma.• The PANWARDS risk score was a sensitive predictor of major ICH in glioma.Venous thromboembolism occurs in up to one-third of patients with primary brain tumors. Spontaneous intracranial hemorrhage (ICH) is also a frequent occurrence in these patients, but there is limited data on the safety of therapeutic anticoagulation. To determine the rate of ICH in patients treated with enoxaparin, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 35 publications
3
75
2
6
Order By: Relevance
“…Our group and others noted a significantly increased risk of ICH in patients with primary brain tumors treated with LMWH compared with no anticoagulation [3,4]. Reassuringly, we did not observe any ICH among the 20 patients with primary brain tumors treated with DOACs, compared with an ICH rate of 18% at 1 year with LMWH.…”
Section: Discussionmentioning
confidence: 82%
“…Our group and others noted a significantly increased risk of ICH in patients with primary brain tumors treated with LMWH compared with no anticoagulation [3,4]. Reassuringly, we did not observe any ICH among the 20 patients with primary brain tumors treated with DOACs, compared with an ICH rate of 18% at 1 year with LMWH.…”
Section: Discussionmentioning
confidence: 82%
“…Besides standard acute recanalization therapies when indicated, these patients sometimes receive empiric long-term anticoagulation because of concerns for cancer-mediated hypercoagulability, and low-molecular-weight heparins are generally preferred over vitamin K antagonists because of extrapolation from randomized trials of venous thromboembolism treatment in patients with cancer (37). However, low-molecular-weight heparins are daily injections, which can be onerous, and are associated with increased bleeding risk, including intracranial hemorrhage (38), which is a major concern for patients with ischemic stroke. Direct oral anticoagulants are another option for cancer-associated thrombosis, although oncological guidelines recommend against their routine use outside of clinical trials (39).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, balancing the risks of thrombosis and hemorrhage is essential, and anticoagulation is generally avoided in patients with a history of previous intracranial hemorrhage, bleeding diathesis, thrombocytopenia (<50,000/μL), coagulopathy, or ongoing life‐threatening extracranial bleeding . A recent matched cohort analysis found that the platelets, albumin, no congestive heart failure, warfarin, age, race, diastolic blood pressure, and stroke score for intracranial hemorrhage, initially developed for risk stratification in patients without cancer, accurately predicted intracranial bleeding in patients with malignant glioma . However, this model must be validated by independent datasets before it can be adopted widely.…”
Section: Patientmentioning
confidence: 99%